2014
DOI: 10.1074/jbc.m113.533885
|View full text |Cite
|
Sign up to set email alerts
|

Structure-guided Development of Specific Pyruvate Dehydrogenase Kinase Inhibitors Targeting the ATP-binding Pocket

Abstract: Background: Up-regulated pyruvate dehydrogenase kinase isoforms (PDKs) are associated with impaired glucose homeostasis in diabetes. Results: Novel PDK inhibitors were developed using structure-based design, which improves glucose tolerance with reduced hepatic steatosis in diet-induced obese mice. Conclusion: Obesity phenotypes are effectively treated by chemical intervention with PDK inhibitors. Significance: PDKs are potential drug targets for obesity and type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(113 citation statements)
references
References 52 publications
4
107
0
2
Order By: Relevance
“…Negatively charged ASP 290 and GLU 262 present in the binding pocket were found to be interacting with the compound. Our results coincide with the active site interaction of (5-Bromo-2, 4-Dihydroxyphenyl)(1,3-Dihydro-2 h-Isoindol- 2-Yl) methanone with ATP binding pocket [18,28]. …”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…Negatively charged ASP 290 and GLU 262 present in the binding pocket were found to be interacting with the compound. Our results coincide with the active site interaction of (5-Bromo-2, 4-Dihydroxyphenyl)(1,3-Dihydro-2 h-Isoindol- 2-Yl) methanone with ATP binding pocket [18,28]. …”
Section: Resultssupporting
confidence: 86%
“…PDK plays a crucial role in glucose utilization and lipid metabolism through pyruvate dehydrogenase complex. In diabetes, PDK2 activity is markedly upregulated and PDK2 has been an emerging therapeutic target for type 2 diabetes as well as a candidate gene for that disease [18]. In our docking study of 4MP2 (Crystal structure of pyruvate dehydrogenase kinase isoform 2 in complex with inhibitor PA1) with the novel compound revealed that ARG 258 forms the strong hydrogen bond interaction with C = O of the novel compound.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies in somatic cells indicate that PDH activity is inhibited by site-specific phosphorylation at three serine residues of the E1 α subunit (PDHE1α): Ser232, Ser293 and Ser300 (Hitosugi et al, 2011;Korotchkina and Patel, 2001;Rardin et al, 2009). To date, four paralogous PDK genes (PDK1-PDK4) have been identified in mammals (Gudi et al, 1995;Tso et al, 2014). PDK1 expression is limited to heart and PDK3 is mainly found in testis, whereas PDK2 can be detected in many tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Recombinant human pyruvate dehydrogenase kinase isoform 2 (PDK2) and its inhibitors (PS10 and PS8) were prepared as described [23]. …”
Section: Methodsmentioning
confidence: 99%